GAPH Survey Forms 358-388 February 1981 - South Georgia Area Planning and Development Commission (Valdosta State University Archives and Special Collections, 1981)
1. 402 W. Screven St., Quitman, Ga. 2. 403 W. Screven St., Quitman, Ga. 3. 210 W. Screven St., Quitman, Ga. 4. 409 W. Screven St., Quitman, Ga. 5. 506 W. Screven St., Quitman, Ga. 6. 508 W. Screven St., Quitman, Ga. 7. 603 W. Screven St., Quitman, Ga. 8. 605 W. Screven St., Quitman, Ga. 9. 606 W. Screven St., Quitman, Ga. 10. 306 W. Screven St., Quitman, Ga.
1 electronic record, PDF, 30 pages, 6241483 bytes.
Keywords: Real Property Surveys; Brooks County (Ga.); Lowndes County Historical Society (Lowndes County, Ga.); Historic Buildings